PENINGKATAN KOSAKATA ANAK KELOMPOK A2 MELALUI MEDIA KARTU GAMBAR SERI DI TK DHARMA INDRIA II KECAMATAN SUMBERSARI KABUPATEN JEMBER TAHUN PELAJARAN 2018/2019 - Bahari, Jon Iskandar; Hasanah, Arizatul (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
Early childhood is an individual who is undergoing a process of rapid and fundamental development for the next life. Early childhood never stops to explore and learn, besides that the child is egocentric, unique, rich in fantasy and the child is at the most potential time for learning. Rapid and fundamental development for the next life. Early childhood has certain characteristics that are distinctive and different from adults, children are always active, dynamic, enthusiastic, have a high curiosity about things that are seen, heard, and felt by children. Early childhood never stops to explore and learn, besides that the child is egocentric, unique, rich in fantasy and the child is at the most potential time for learning. This research will be conducted at Kindergarten Dharma Indria II, Sumbersari District, Jember Regency. Observation activities during the learning process include observing teacher teaching and learning activities of children in class. This activity was assisted by 4 observers, namely group A teacher, Umud Nuril ‘Aini, Puji Nurul Avini, and Tsalistatul Mas’udah. The researcher acts as the teacher observed by the A2 group teacher, Mother. Miftah fardhiyah, while Umud Nuril ‘Aini was in charge of observing the red group children, Puji Nurul Avini observed the yellow group children, and Tsalistatul Mas' had observed the green group children. Observations to teachers are made to assess the suitability of teacher teaching activities with the daily activity plan (RKH)